2011
DOI: 10.1111/j.1365-2230.2010.03996.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin-17 is correlated with interferon-α expression in cutaneous lesions of lupus erythematosus

Abstract: Two major cytokines, IL-17A and IFN-α, may play roles in the pathogenesis of CLE. Their patterns of expression positively correlated with each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 53 publications
(104 reference statements)
2
32
0
Order By: Relevance
“…Several reports have described the presence of IL-17 related activity or signals in DLE lesions by immunohistochemistry (Oh et al , 2011; Tanasescu et al , 2010) or in the serum of DLE patients (Balanescu et al , 2010). IL-17-related markers have also been reported as upregulated compared to healthy controls in the serum of SLE patients in some (Shah et al , 2010; Zhao et al , 2010), but not all (Brajac et al , 2010; Higgs et al , 2012)) studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the presence of IL-17 related activity or signals in DLE lesions by immunohistochemistry (Oh et al , 2011; Tanasescu et al , 2010) or in the serum of DLE patients (Balanescu et al , 2010). IL-17-related markers have also been reported as upregulated compared to healthy controls in the serum of SLE patients in some (Shah et al , 2010; Zhao et al , 2010), but not all (Brajac et al , 2010; Higgs et al , 2012)) studies.…”
Section: Discussionmentioning
confidence: 99%
“…Within the disease setting of JSLE the PBMCs may be similarly activated once they have migrated to disease affected organs. Notably, IL-17 + infiltrating T cells have previously been detected in the kidney’s of adult SLE patients [21] and IL-17A protein has been found in cutaneous lesions of adult SLE patients [22]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that serum IL-17 levels are also elevated in SLE patients compared to controls (Vincent et al, 2013; Wong et al, 2008) and the Th17 pathway has been shown to drive autoimmune responses in pre-clinical mouse models of lupus (Hsu et al, 2008; Jacob et al, 2009). More importantly, IL-17 and IL-17 producing cells are also been detected in kidney tissue and skin biopsies from SLE patients (Crispin et al, 2008; Oh et al, 2011; Yang et al, 2009), suggesting a possible role for IL-17 in the pathophysiology of SLE and a potential therapeutic option of using anti-IL-17A in treating patients with SLE.…”
Section: Role Of Il-17a In Autoimmune Diseasesmentioning
confidence: 99%